Answer:
[tex]b=\dfrac{2\pm3\sqrt{2}}{2}[/tex]
Step-by-step explanation:
Rearrange so the equation is in the general form of a quadratic equation [tex]ax^2+bx+c=0[/tex]
[tex]\implies 2b^2-4b-7=0[/tex]
Replace b with x (we will change this back at the end, but this is to avoid confusion when using the quadratic formula):
[tex]\implies 2x^2-4x-7=0[/tex]
Therefore, comparing the equation with [tex]ax^2+bx+c=0[/tex]
Use the quadratic formula to solve, inputting the above values:
[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac} }{2a}[/tex]
[tex]\implies x=\dfrac{-(-4)\pm\sqrt{(-4)^2-4(2)(-7)} }{2(2)}[/tex]
[tex]\implies x=\dfrac{4\pm\sqrt{72}}{4}[/tex]
[tex]\implies x=\dfrac{4\pm6\sqrt{2}}{4}[/tex]
[tex]\implies x=\dfrac{2\pm3\sqrt{2}}{2}[/tex]
Finally, change x back to b:
[tex]b=\dfrac{2\pm3\sqrt{2}}{2}[/tex]